Pemanfaatan Digital Marketing Bagi Universitas Islam Al-Azhar (Unizar) - Danang Priyo Jatmiko; Hendri Purnomo; Bayu Wibisana (Universitas Islam Al-Azhar Mataram, 2023)
Digitalization an important role as a marketing media and transmission of academic/non-academic information. Therefore, analysis related to optimizing the use of digital marketing for Unizar. The hope, using digital marketing to expand the range of Unizar promotions to remote areas. Al-Azhar Islamic University (UNIZAR) is one of the oldest and well-known campus on Lombok Island, starting to develop digital systems in various aspects that support campus activities. UNIZAR realizes that digital marketing can reach all people wherever they are without any geographical or time boundaries. The digital system that UNIZAR has begun to use includes in the academic field using the Academic System called SIAKAD UNIZAR, as well as in utilizing social media as a means of massive promotion and publication. Even though Unizar has used digitization, its utilization is considered not optimal. This is of particular concern, because digitization plays an important role as a marketing medium or delivery of academic and non-academic information. Therefore, it is necessary to carry out an analysis related to optimizing the use of digital marketing for Unizar.. Digital marketing to promote Unizar using social media such as Facebook, Instagram and YouTube. The use of Instagram, and Youtube are social media with the most users, so it's more efficient to promote Unizar. And now time to change to use digital marketing in order to increase the number of prospective new students Unizar